The mapmakers - Merchant, Tamzin (Norton Young Readers, 2022)
Cordelia Hatmaker has saved England from war, but danger is lurking around every corner, and she must convince the rival Maker families to work together for once--not only to bring her father home, but also to save the very essence of magic itself.